2017
DOI: 10.1680/jstbu.16.00084
|View full text |Cite
|
Sign up to set email alerts
|

Flexural properties as a basis for bamboo strength grading

Abstract: Abstract:Current design and construction codes and standards for bamboo do not contain strength grading procedures beyond cursory visual inspections. This deficiency arguably limits the safe and economic use of the material. This paper presents findings from an international research project which seeks to develop a strength grading system for bamboo culms. Over 200 four-point bending tests were carried out on Guadua angustifolia Kunth (Guadua a.k.) culms for which numerous mechanical and physical properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 4 publications
5
40
0
Order By: Relevance
“…In terms of failure, the five samples presented four cracks which developed suddenly along the central third of the culm, each crack distributed at approximately 90 degrees ( Figure 5) around the pole's circumference. A high percentage of failure cases has been reported in the literature [10,18] as caused by shear or crushing around the points of application of the loads. This failure behaviour does not represent the characteristic failure of a bending test of thin-walled tubes and might be caused by a local effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of failure, the five samples presented four cracks which developed suddenly along the central third of the culm, each crack distributed at approximately 90 degrees ( Figure 5) around the pole's circumference. A high percentage of failure cases has been reported in the literature [10,18] as caused by shear or crushing around the points of application of the loads. This failure behaviour does not represent the characteristic failure of a bending test of thin-walled tubes and might be caused by a local effect.…”
Section: Resultsmentioning
confidence: 99%
“…During the last 20 years, researchers have focused on the determination of bamboo geometric [6][7][8] and mechanical [9][10][11] properties with the aim of characterising the material and provide engineering support for the structural implementation of bamboo elements, however, the application of conventional methodologies for material characterisation have not been adequate for bamboo due to the complexity of its geometric and mechanical characteristics. On one hand, the geometric characteristics of bamboo include tapering; nodes randomly distributed along the height; section properties varying along the pole; and out-of-straightness [12].…”
Section: Introductionmentioning
confidence: 99%
“…He found that the main geometric variabilities on the geometry of bamboo were due to a) tapering, b) irregular internodal distances, c) variable cross sectional properties along its axis and d) out-of-straightness. As such, the accurate determination of geometric properties is fundamental to study the mechanical properties of round bamboo [7][8][9][10][11], behaviour of connections [12,13] and structural analysis [14,15] for which determining the pole's geometric variability is fundamental. Nevertheless, the only official international standard, ISO 22157-1-2004 [16], focused on the determination of the physical and mechanical properties of bamboo, is based on basic measurements of a limited and discrete number of properties that fail to capture the significant variation in the geometry of bamboo poles described by Janssen [6].…”
Section: Natural Geometrymentioning
confidence: 99%
“…Since only lignin matrix takes place for bamboo endurance during loading in transverse direction. [35] suggested treating bamboo as structural element instead of material, therefore bending stiffness (EI) is more appropriate than modulus of elasticity. The moment of inertia (I) was calculated as follows:…”
Section: Mechanical Properties Of Bamboomentioning
confidence: 99%